The Prevailing Organizational Culture from the Perspective of the Quran and the Sunnah: Case Study of an Islamic Charity Association in Palestine - Nassr, Salem Khalil (Journal of Islamic and Social Studies, 2024)
The reality of the occupation and the repeated offensives the Palestinian people lived through every day across Palestine doubled the number of orphans. The resulting political and institutional need for the effective management of institutions that care for orphans in various governorates increased. This study aimed to identify the most important features of organizational behavior derived from the Holy Qur’an and the Sunnah of the Prophet, according to which work is carried out in the Dora Islamic Society for Orphan Care. The research problem was chosen to identify the main challenges facing this charity in managing its operations and to explore the strategies it uses to overcome these challenges. The study used the descriptive approach to study the descriptive case, which is the charity. The study used the interview tool, so the questions and topics that were discussed were developed, and answers to their questions were obtained with the charity’s team through interviews. The work of the charity stems strongly from the legal foundation of the disposal of (clean) money for the benefit of orphan care. The charity has become a reference for hundreds of needy families and a point of trust for them. The results indicated that the prevailing organizational behavior in the charity is linked to the Sharia rulings, and each procedure is tried according to its legislative principles. The team was genuine and reflective of strong trust internally, as well as a strong relationship between the servant leader style of the CEO and the rest of the team members.